Hybrid metal halide crystalline material with thermally induced jumping behavior and method of preparation thereof

CN121137802BActive Publication Date: 2026-10-30NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511028064.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2026-10-30
Estimated Expiration
2045-07-24

AI Technical Summary

Technical Problem

但调控手段主要集中在改变有机组分,限制了跳跃晶体结构多样性的开发

Benefits of technology

[0043]本发明利具有三个氨基支链的刚性嘧啶环的有机胺和无机金属卤化物四面体自组装形成有机无机杂化金属卤化物,氨基和嘧啶环的N原子提供了丰富的氢键位点,形成了有机胺逐层排列,无机卤素四面体插层分布的晶体结构。有机胺与无机四面体的卤素间通过氢键相互作用维持层内稳定性,在晶体学c轴方向有机胺的层状堆叠赋予了它们各向异性的热膨胀系数。在毫秒级的时间尺度上应力的快速释放实现热能向机械能的转换,使其具有移动、跳跃、分裂等多种运动形式。在小于3ms时间内的应力释放可以赋予晶体超过5.37m/s的平均速度。将卤素C1替换为Br后,原子半径和密度的增大削弱了各向异性程度,使跳跃启动温度提高了50K以上,这一思路为设计合成更丰富的动态晶体提供了新思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121137802B_ABST
    Figure CN121137802B_ABST
Patent Text Reader

Abstract

The application discloses a hybrid metal halide crystal material with thermal jump properties, which is characterized by being synthesized from an organic amine ligand and a metal halide and having a dynamic response crystal under thermal stimulation. The preparation method comprises the following steps: dissolving the metal halide and the organic amine ligand in a hydrogen halide solution, obtaining a milky white suspension through ultrasonic or magnetic stirring; adding anhydrous methanol and deionized water into the suspension respectively, and magnetically stirring under heating until complete dissolution to obtain a clear solution; after being cooled to room temperature, the container containing the clear solution is sealed in a gas-permeable manner to slow down the volatilization of the liquid, and block-shaped crystals are obtained after standing and volatilization. The size of the crystals can be adjusted by adjusting the proportion of the ternary mixed solvent, and the jump starting temperature can be increased by about 50 K through a halogen substitution strategy. The method has the advantages of simple process and mild conditions, realizes the regulation of the thermal response behavior through crystal structure design, and has application values in the fields of thermal driving micro-actuators, thermal switch devices and solid-state sensors.
Need to check novelty before this filing date? Find Prior Art

Description

(I) Technical Field:

[0001] This invention belongs to the field of dynamic crystal materials technology, and relates to hybrid metal halide materials with thermally induced jumping behavior and their preparation methods. (II) Background Technology:

[0002] Dynamic crystals are a class of crystalline materials that exhibit various mechanical responses to external stimuli such as light, heat, electricity, and pressure, including shape changes (bending, translation, torsion) and motions (jumping, rotation, etc.). Among them, thermo-jumping crystals, as an important branch of dynamic crystals, have attracted widespread attention due to their ability to rapidly convert thermal energy into kinetic energy, exhibiting characteristics such as short response time and high energy efficiency. They hold promise for applications in thermal response materials for electromechanical equipment, actuators, electronics, or sensors. Leveraging the long-range order and close-packed structure of crystals, local molecular perturbations generate localized stresses within the densely packed lattice. These stresses are amplified in time and space through coordinated molecular motion, thus exhibiting mechanical responses or self-driving mechanisms.

[0003] Currently, most thermo-induced jumping crystals are found in organic molecular systems. Strategies such as designing molecular motors and introducing volatile small molecules through co-crystallization have been developed. Thermal stimulation alters the molecular configuration or causes small molecules to overflow, generating stress that drives crystal movement. However, the control methods mainly focus on changing the organic composition, limiting the development of diverse jumping crystal structures. Organic-inorganic hybrid metal halide crystals, as a class of crystalline materials formed by the self-assembly of organic molecules and inorganic polyhedra, can have their structure altered by adjusting the types and proportions of metal ions, halide ions, and organic molecules, thereby regulating the material's band gap, electronic conductivity, and optical properties. With their high structural flexibility, efficient optoelectronic properties, and excellent processability, they have broad application potential in optoelectronic devices and other fields, providing a new and ideal platform for the further development and expansion of dynamic crystals.

[0004] Therefore, existing thermo-jumping crystals are mainly limited to organic molecular systems. To break through the bottleneck of structural design and achieve rich structural tunability and property diversity, developing hybrid metal halide crystals with thermo-jumping properties is one of the core challenges in designing next-generation stimulus-responsive materials. (III) Summary of the Invention:

[0005] In view of the problems and improvement needs of the existing technology, the present invention aims to provide a hybrid metal halide crystal material with thermally induced jumping properties and its preparation method. The crystal has a periodic structure with organic components arranged in layers and inorganic metal halide tetrahedral intercalation, and features diverse motion modes, short response time, adjustable jumping start temperature, and simple preparation process.

[0006] To achieve the above objectives, the present invention provides the following solution:

[0007] A hybrid metal halide crystal material with thermo-induced jumping properties is synthesized from organic amine ligands and metal halides, and exhibits a dynamic response under thermal stimulation.

[0008] The hybrid metal halide crystal material has a periodic structure in which organic components are arranged in layers and inorganic halogen tetrahedra are distributed between the layers, with its space group being R3.

[0009] The general structural formula of the hybrid metal halide crystal material is ABX4, where A is an organic ligand, B is a metal ion, and X is a halogen.

[0010] The organic amine ligand is a rigid aromatic heterocyclic organic amine containing polyamino branches.

[0011] The organic amine ligand is 2,4,6-triaminopyrimidine.

[0012] The structural formula of the 2,4,6-triaminopyrimidine is as follows:

[0013]

[0014] The metal halide is zinc chloride, cobalt chloride, zinc bromide, or cobalt bromide.

[0015] The hybrid metal halide crystal material has a near-cubic bulk crystal appearance.

[0016] When the metal halide is zinc chloride and zinc bromide, and the organic amine ligand is 2,4,6-triaminopyrimidine, the crystal chemical formulas are C4H9N5ZnCl4 and C4H9N5ZnBr4, respectively, denoted as TAPZnCl4 and TAPZnBr4, where TAP = 2,4,6-triaminopyrimidine.

[0017] The unit cell parameters of the 2,4,6-triaminopyrimidine zinc chloride are as follows: α=β=90°, γ=120°;

[0018] The unit cell parameters of the 2,4,6-triaminopyrimidine zinc bromide are as follows: α=β=90°, γ=120°.

[0019] The 2,4,6-triaminopyrimidine zinc chloride and 2,4,6-triaminopyrimidine zinc bromide exhibited broad-spectrum blue-white fluorescence emission under 360 nm excitation, with central peak positions of 455 nm and 465 nm, respectively.

[0020] DSC and TG tests of the 2,4,6-triaminopyrimidine zinc chloride and 2,4,6-triaminopyrimidine zinc bromide showed that the jump start temperature ranges were 404-421K and 460-475K, respectively, and the decomposition temperatures were 510K and 540K, respectively. After replacing the halogen Cl with Br, the thermally driven jump start temperature increased by more than 50K.

[0021] The 2,4,6-triaminopyrimidine zinc chloride exhibits anisotropic thermal expansion coefficients upon heating, with crystallographic a-axis and c-axis thermal expansion coefficients of 20.95 M·K⁻¹. 1 and 73.17 M·K- 1 The coefficient of thermal expansion along the c-axis is 3.49 times that along the a-axis.

[0022] The c-axis thermal expansion coefficient of the 2,4,6-triaminopyrimidine zinc bromide decreased to 66.30 M·K⁻¹ after replacing the halogen Cl with Br. 1 The coefficient of thermal expansion along the a-axis increases to 22.40 M·K⁻¹. 1 The ratio of the thermal expansion coefficient of the c-axis to that of the a-axis decreases to 2.95 times.

[0023] The hybrid metal halide crystal material with thermally induced jumping properties exhibits various forms of motion under thermal stimulation, such as jumping, moving, or cleavage splitting; the high-speed camera captures the jump start time in less than 2.5ms, the moving response time in less than 8ms, and the cleavage splitting response time in less than 2.5ms.

[0024] The present invention also provides a method for preparing the hybrid metal halide crystal material with thermally induced jumping properties, the specific steps of which are as follows:

[0025] (1) Dissolve the metal halide and organic amine ligand in a hydrogen halide solution and obtain a milky white suspension by ultrasonic or magnetic stirring;

[0026] (2) Add anhydrous methanol and deionized water to the suspension respectively, and stir magnetically under heating until completely dissolved to obtain a clear solution;

[0027] (3) After cooling to room temperature, the container containing the clear solution obtained in step (2) is sealed with a breathable seal to slow down the evaporation of the liquid. After standing and evaporating, blocky crystals are obtained.

[0028] In step (1), the molar ratio of the metal halide to the organic amine ligand is 1:1.

[0029] In step (1), the ratio of hydrogen halide solution to metal halide is hydrogen halide: metal halide = 6 ml: 1 mmol.

[0030] In step (1), the metal halide is one of zinc chloride, zinc bromide, cobalt chloride, or cobalt bromide;

[0031] In step (1), the organic amine ligand is 2,4,6-triaminopyrimidine;

[0032] In step (1), the hydrogen halide solution is a hydrobromic acid aqueous solution with a concentration of 40-48% or 99% hydrochloric acid.

[0033] In step (2), when the volume ratio of hydrogen halide: anhydrous methanol: deionized water is 2:2:1, it is easy to grow crystals with a side length less than 0.8 mm; when the volume ratio of hydrogen halide: anhydrous methanol: deionized water is 3:2:2, it is easy to grow crystals with a side length greater than 0.8 mm.

[0034] The heating temperature in step (2) is between 50 and 100°C.

[0035] In step (3), the temperature is lowered to room temperature at a rate of 5℃ / min, the container containing the clear solution is sealed with a sealing film, and a hole is made with a needle tip. The solution is slowly evaporated at a rate of 0.02ml / h at room temperature, and blocky crystals are obtained after 1-7 days.

[0036] When the metal halide is zinc chloride and the organic amine ligand is 2,4,6-triaminopyrimidine, the specific steps for preparing hybrid metal halide crystals with thermo-induced jumping properties are as follows:

[0037] Step 1: Weigh zinc chloride and 2,4,6-triaminopyrimidine in a molar ratio of 1:1 and place them in an open glass bottle. Add hydrochloric acid at a ratio of 6 ml to 1 mmol of zinc chloride. Seal the bottle and stir with ultrasound or magnetic force to obtain a milky white suspension.

[0038] Step 2: Add anhydrous methanol and deionized water to the suspension according to the volume ratio of hydrochloric acid: anhydrous methanol: deionized water = 2:2:1 or 3:2:2. Stir magnetically under heating conditions of 50-100℃ until completely dissolved to obtain a clear solution.

[0039] Step 3: Slowly cool to room temperature, seal the open bottle with sealing film, and poke a few holes with a needle tip to slow down the evaporation rate. After standing for 1-7 days, block crystals are obtained. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc chloride crystal material is obtained.

[0040] This invention also provides the application of hybrid metal halide crystal materials with thermally induced jumping properties in protection circuits:

[0041] The hybrid halide crystal is used as a thermal switching device in the protection circuit. The hybrid halide crystal is placed on a conductive heating plate as a thermal switching device. One end of the power supply of the circuit is connected to the conductive heating plate, and the other end is placed above the crystal. Since the insulating crystal separates the electrodes, the circuit is in the off state at ambient temperature. When the temperature of the conductive heating plate reaches the crystal jump start temperature, the crystal jumps and the circuit is in the connected state.

[0042] The present invention discloses the following technical effects:

[0043] This invention utilizes the self-assembly of organic amines with rigid pyrimidine rings possessing three amino branches and inorganic metal halide tetrahedra to form organic-inorganic hybrid metal halides. The nitrogen atoms of the amino and pyrimidine rings provide abundant hydrogen bonding sites, resulting in a crystal structure where the organic amines are arranged in layers and the inorganic halogens are intercalated in tetrahedra. Hydrogen bonding maintains intralayer stability between the organic amines and the inorganic tetrahedra, and the layered stacking of the organic amines along the crystallographic c-axis imparts anisotropic thermal expansion coefficients. Rapid stress release on a millisecond timescale enables the conversion of thermal energy into mechanical energy, allowing for various forms of motion such as movement, jumping, and splitting. Stress release within less than 3 ms can endow the crystal with an average velocity exceeding 5.37 m / s. Replacing the halogen Cl with Br increases the atomic radius and density, weakening the anisotropy and raising the jumping initiation temperature by more than 50 K. This approach provides a new direction for designing and synthesizing more dynamic crystals.

[0044] This invention involves dissolving a metal halide and 2,4,6-triaminopyrimidine in a ternary mixed solvent of hydrogen halide / methanol / water at a specific molar ratio. The solution is then homogenized by ultrasonic or heating stirring. Crystallization is achieved by puncturing a sealed membrane with a pinhole and allowing the solution to stand at room temperature (25±3℃) for 1-7 days. The resulting crystals are then washed, filtered, and dried to obtain bulk single crystals. The crystal size can be adjusted by changing the ratio of the ternary mixed solvent. A halogen substitution strategy (Cl→Br) can raise the jump-start temperature by approximately 50K (DSC verification). This method is simple, operates under mild conditions, and achieves control over thermal response behavior through crystal structure design. It has application value in the fields of thermally driven micro-actuators, thermal switching devices, and solid-state sensors. (iv) Description of the attached drawings:

[0045] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0046] Figure 1-1 , Figure 1-2The PXRD pattern of the hybrid metal halide crystal material with thermally induced jumping properties is shown in the embodiment of the present invention.

[0047] Figure 2-1 , Figure 2-2 This is a structural diagram of the 2,4,6-triaminopyrimidine zinc chloride crystal material according to an embodiment of the present invention. Figure 2-1 Projected along the b-axis direction. Figure 2-2 Projected along the c-axis;

[0048] Figure 3-1 , Figure 3-2 This is a structural diagram of the 2,4,6-triaminopyrimidine zinc bromide crystal material according to an embodiment of the present invention. Figure 3-1 Projected along the b-axis direction. Figure 3-2 Projected along the c-axis;

[0049] Figure 4-1 , Figure 4-2 The images show the ultraviolet absorption spectrum and fluorescence emission spectrum of the thermo-jumping hybrid metal halide according to an embodiment of the present invention;

[0050] Figure 5-1 , Figure 5-2 Thermogravimetric analysis of hybrid metal halides with thermally induced jumping properties according to an embodiment of the present invention;

[0051] Figure 6-1 , Figure 6-2 Differential scanning calorimetry curves of hybrid metal halides with thermally induced jumping properties according to embodiments of the present invention;

[0052] Figure 7-1 , Figure 7-2 This is a fitting diagram of the thermal expansion coefficient of the hybrid metal halide with thermally induced jumping properties according to an embodiment of the present invention;

[0053] Figure 8-1 , Figure 8-2 This is a crystal appearance diagram of a hybrid metal halide with thermally induced jumping properties according to an embodiment of the present invention;

[0054] Figure 9 The image shows the trajectory of jumping, moving, and dissociating / fragmenting of the 2,4,6-triaminopyrimidine zinc chloride crystal material captured by a high-speed camera in an embodiment of the present invention.

[0055] Figure 10 This is a statistical diagram of the motion behavior of 2,4,6-triaminopyrimidine zinc chloride crystal material at different sizes according to an embodiment of the present invention;

[0056] Figure 11 The displacement and average velocity in the vertical direction of the 2,4,6-triaminopyrimidine zinc chloride crystal material in this embodiment of the invention;

[0057] Figure 12-1 , Figure 12-2 This is a schematic diagram illustrating the practical application of 2,4,6-triaminopyrimidine zinc chloride crystal material as a temperature control switch in an overheat protection circuit, according to an embodiment of the present invention. (V) Specific Implementation Methods:

[0058] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0059] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0060] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to documents in this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated references, the contents of this specification shall prevail.

[0061] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0062] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0063] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased on the market or prepared by existing methods.

[0064] Example 1: Preparation of small-sized 2,4,6-triaminopyrimidine zinc chloride crystals:

[0065] 1 mmol of 2,4,6-triaminopyrimidine (98%) and 1 mmol of zinc chloride (98%) were weighed separately and placed in a 20 ml transparent glass screw-top bottle. 6 ml of hydrochloric acid (99%) was added, and the mixture was sonicated to obtain a white suspension. Under magnetic stirring at 80 °C, 6 ml of methanol (99.5%) and 3 ml of deionized water were added sequentially. After approximately 10 minutes, a clear, transparent solution was obtained. The solution was slowly cooled to room temperature at a rate of 5 °C / min. The open bottle was sealed with sealing film, and a few holes were made with a needle tip. The solution was allowed to evaporate slowly at a rate of 0.02 ml / h at room temperature. After standing for 1–7 days, blocky crystals appeared at the bottom of the bottle. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc chloride crystals with a side length less than 0.8 mm were obtained. The chemical formula of the crystals is C4H9N5ZnCl4, denoted as TAPZnCl4, where TAP = 2,4,6-triaminopyrimidine.

[0066] Example 2: Preparation of small-sized 2,4,6-triaminopyrimidine zinc bromide crystals:

[0067] 1 mmol of 2,4,6-triaminopyrimidine (98%) and 1 mmol of zinc bromide (98%) were weighed separately and placed in a 20 ml transparent glass screw-top bottle. 6 ml of hydrobromic acid (40%) was added, and the mixture was sonicated to obtain a milky white suspension. Under magnetic stirring at 80 °C, 6 ml of methanol (99.5%) and 3 ml of deionized water were added sequentially. After approximately 10 minutes, a clear, transparent solution was obtained. The solution was slowly cooled to room temperature at a rate of 5 °C / min. The open bottle was sealed with sealing film, and a few holes were made with a needle tip. The solution was allowed to evaporate slowly at a rate of 0.02 ml / h at room temperature. After standing for 1–7 days, blocky crystals appeared at the bottom of the bottle. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc bromide crystals with a side length less than 0.8 mm were obtained. The chemical formula of the crystal is C4H9N5ZnBr4, denoted as TAPZnBr4, where TAP = 2,4,6-triaminopyrimidine.

[0068] Example 3: Preparation of large-sized 2,4,6-triaminopyrimidine zinc chloride crystals:

[0069] 1 mmol of 2,4,6-triaminopyrimidine (98%) and 1 mmol of zinc chloride (98%) were weighed separately and placed in a 20 mL transparent glass screw-top bottle. 6 mL of hydrochloric acid (99%) was added, and the mixture was sonicated to obtain a white suspension. Under magnetic stirring at 80 °C, 4 mL of methanol (99.5%) and 4 mL of deionized water were added sequentially. After approximately 10 minutes, a clear, transparent solution was obtained. The solution was slowly cooled to room temperature at a rate of 5 °C / min. The open bottle was sealed with sealing film, and a few holes were made with a needle tip. The solution was allowed to evaporate slowly at a rate of 0.02 mL / h at room temperature. After standing for 1–7 days, blocky crystals appeared at the bottom of the bottle. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc chloride crystals with a side length greater than 0.8 mm were obtained. The chemical formula of the crystals is C4H9N5ZnCl4, denoted as TAPZnCl4, where TAP = 2,4,6-triaminopyrimidine.

[0070] Example 4: Preparation of large-size 2,4,6-triaminopyrimidine zinc bromide crystals:

[0071] 1 mmol of 2,4,6-triaminopyrimidine (98%) and 1 mmol of zinc bromide (98%) were weighed and placed in a 20 ml transparent glass screw-top bottle. 6 ml of hydrobromic acid (40%) was added, and the mixture was sonicated to obtain a milky white suspension. Under magnetic stirring at 80 °C, 4 ml of methanol (99.5%) and 4 ml of deionized water were added sequentially. After approximately 10 minutes, a clear, transparent solution was obtained. The solution was slowly cooled to room temperature at a rate of 5 °C / min. The open bottle was sealed with sealing film, and a few holes were made with a needle tip. The solution was allowed to evaporate slowly at a rate of 0.02 ml / h at room temperature. After standing for 1–7 days, blocky crystals appeared at the bottom of the bottle. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc bromide crystals with a side length greater than 0.8 mm were obtained. The chemical formula of the crystal is C4H9N5ZnBr4, denoted as TAPZnBr4, where TAP = 2,4,6-triaminopyrimidine.

[0072] The hybrid metal halide crystal materials 2,4,6-triaminopyrimidine zinc chloride crystal and 2,4,6-triaminopyrimidine zinc bromide crystal with thermally induced jumping properties have a periodic structure in which organic components are arranged in layers and inorganic halogen tetrahedra are distributed in the interlayer, and their space group is R3.

[0073] The structural formula of the 2,4,6-triaminopyrimidine is as follows:

[0074]

[0075] The unit cell parameters of the 2,4,6-triaminopyrimidine zinc chloride are as follows: α=β=90°, γ=120°;

[0076] The unit cell parameters of the 2,4,6-triaminopyrimidine zinc bromide are as follows: α=β=90°, γ=120°;

[0077] The hybrid metal halide crystal materials, 2,4,6-triaminopyrimidine zinc chloride crystal and 2,4,6-triaminopyrimidine zinc bromide crystal, are nearly cubic blocky crystals.

[0078] In the embodiments,

[0079] The purity of the hybrid metal halide crystal materials prepared in the examples was verified using X-ray powder diffraction (XPD). A Rigaku MiniFlex 600 diffractometer equipped with a copper target was used, with the operating voltage set to 40 kV and the operating current to 100 mA. The sample was placed on a clean silicon wafer, flattened with a doctor blade, and the test conditions were set to a scan rate of 5 deg / min and a 2θ of 10-50° to obtain the PXRD pattern. The results are as follows: Figure 1-1 , Figure 1-2 As shown, the test peaks of powder diffraction correspond one-to-one with the theoretically fitted peaks, verifying the high purity of the powder. The crystal structure is as follows: Figure 2-1 , Figure 2-2 and Figure 3-1 , Figure 3-2 As shown.

[0080] The spectral absorption range of the hybrid metal halide crystal materials prepared in the examples was measured using a UV-Vis absorption spectrometer, with barium sulfate as a standard, within the wavelength range of 200-650 nm. The results are as follows: Figure 4-1 , Figure 4-2 As shown, the main absorption peaks of the hybrid metal halide crystals are in the wavelength range of 200-350 nm. Fluorescence spectra were collected using a 360 nm laser. Both 2,4,6-triaminopyrimidine zinc chloride and 2,4,6-triaminopyrimidine zinc bromide crystals exhibited broad-spectrum blue-white fluorescence emission in the 400-600 nm range, with central peaks at 455 nm and 465 nm, respectively.

[0081] The thermal stability of the hybrid metal halide crystals prepared in the examples was tested using a thermogravimetric analyzer. A 6 mg sample was tested under an argon atmosphere using an alumina crucible. The scanning temperature range was from room temperature to 800 °C, and the scan rate was 10 °C / min. The results are as follows: Figure 5-1 , Figure 5-2As shown, the thermogravimetric curves reveal that 2,4,6-triaminopyrimidine zinc chloride exhibits a 67.9% stepwise weight loss at 404-421 K and begins to decompose at 510 K, while 2,4,6-triaminopyrimidine zinc bromide exhibits a 15.7% stepwise weight loss at 460-475 K and begins to decompose at 540 K. This indicates that the crystals possess good thermal stability, and this stepwise weight loss is due to the weight loss caused by the crystals jumping out of the open crucible when heated.

[0082] The thermal effects of the hybrid metal halide crystal materials prepared in the examples were tested using differential scanning calorimetry. 5 mg of powder sample was weighed, compacted in an aluminum crucible, and tested under a nitrogen atmosphere in the range of room temperature to 490 K. The temperature was increased from room temperature to 490 K at a rate of 10 °C / min, then decreased to room temperature at a rate of 10 °C / min, and the cycle was repeated at the same rate. The results are as follows. Figure 6-1 , Figure 6-2 As shown, 2,4,6-triaminopyrimidine zinc chloride and 2,4,6-triaminopyrimidine zinc bromide have serrated endothermic peaks in the ranges of 404-421 K and 460-475 K, respectively. This is because different crystals have different jump start temperatures. The endothermic peaks disappear during cycling, indicating the single-jump property of the crystals.

[0083] The single-crystal structure of the hybrid metal halide crystal materials prepared in the examples was tested using a single-crystal X-ray diffractometer. Data were collected at different temperatures ranging from 320K to 450K using a temperature control accessory. The crystal structure and unit cell parameters were obtained through structural refinement, and the thermal expansion coefficients of the crystal axes were fitted using PASCal software. The results are as follows: Figure 7-1 , Figure 7-2 As shown, the crystal structure exhibits anisotropy upon heating, specifically the anisotropic coefficient of thermal expansion of the 2,4,6-triaminopyrimidine zinc chloride crystal structure upon heating. The crystallographic coefficients of thermal expansion along the a-axis and c-axis are 20.95 M·K⁻¹, respectively. 1 and 73.17 M·K- 1 The coefficient of thermal expansion along the c-axis is 3.49 times that along the a-axis.

[0084] The c-axis thermal expansion coefficient of the 2,4,6-triaminopyrimidine zinc bromide decreased to 66.30 M·K⁻¹ after replacing the halogen Cl with Br. 1 The coefficient of thermal expansion along the a-axis increases to 22.40 M·K⁻¹. 1 The ratio of the thermal expansion coefficient of the c-axis to that of the a-axis decreases to 2.95 times.

[0085] like Figure 8-1 , Figure 8-2 As shown, the crystal plane index corresponding to the naturally grown crystal plane is obtained by calibrating the crystal plane using single-crystal X-ray diffraction.

[0086] The motion trajectory of the hybrid metal halide crystal material prepared in the examples was captured using a high-speed camera. The camera used was a Wolf 5KF10, with a frame rate of 1600 frames per second and a resolution of 1280×720. Figure 9 As shown, crystals exhibit various forms of motion under thermal stimulation, such as jumping, moving, or cleavage. A high-speed camera captures the start-up time of jumping (less than 2.5 ms), the response time of moving (less than 8 ms), and the response time of cleavage (less than 2.5 ms). Figure 10 As shown, the motion pattern of crystals is related to their size. Crystals with a side length less than 0.6 mm exhibit small motion amplitudes, tending towards stillness and movement, with a lower probability of jumping. Conversely, crystals with a side length greater than 0.8 mm have a significantly increased probability of jumping. Figure 11 As shown, a crystal with a side length of 0.8 mm produced a vertical displacement of 16.1 mm within 3.0 ms, and the calculated average velocity exceeded 5.37 m / s.

[0087] The circuit elements in the described circuit are interconnected along a single path to form a series circuit, including a DC power supply, an LED bulb as a load, and a hybrid metal halide crystal as a thermal switch. One end of the power supply is connected to a conductive heating plate, the crystal is placed on the heating plate, and the other end is positioned above the crystal. Because the insulating crystal separates the electrodes, the circuit is in the off state at ambient temperature. When the heating plate temperature reaches T ± 10 K, the crystal jumps, and the circuit is in the connected state, where T is 410 K or 460 K.

[0088] like Figure 12-1 , Figure 12-2 As shown, using a 3.6V DC power supply, wires, and an LED bulb as circuit components, the hybrid metal halide crystal material prepared in the example is placed on a heating stage. One end is connected to the positive terminal of the power supply via a wire, and the other end is connected to the bulb via the conductive heating stage to form a series circuit. A thermocouple is used to monitor the contact temperature of the heating stage surface in real time. Figure 12-1 , Figure 12-2 As shown, TAPZnCl4 crystal is used as a temperature control switch in the circuit. Since the crystal is non-conductive, the current in the initial circuit is zero. When the temperature exceeds 410K, the crystal is heated and jumps away from its initial position, causing the upper wire to fall onto the hot platform. At this point, the protection circuit is activated, the bulb is lit, and the current changes from 0 to 0.03A. This device demonstrates that the hybrid metal halide crystal material prepared in this embodiment can be used as a temperature control switch in a protection circuit, and has application value in the fields of thermal switching devices and solid-state sensors.

[0089] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A hybrid metal halide crystal material with thermally induced jumping properties, characterized in that... It is a crystal synthesized from organic amine ligands and metal halides, which exhibits a dynamic response under thermal stimulation; the crystal chemical formulas are C4H9N5ZnCl4 or C4H9N5ZnBr4, denoted as TAPZnCl4 or TAPZnBr4, where TAP = 2,4,6-triaminopyrimidine.

2. The hybrid metal halide crystal material with thermally induced jumping properties according to claim 1, characterized in that... The hybrid metal halide crystal material has a periodic structure in which organic components are arranged in layers and inorganic halogen tetrahedra are distributed between the layers, with its space group being R3.

3. The hybrid metal halide crystal material with thermally induced jumping properties according to claim 1, characterized in that... The organic amine ligand is 2,4,6-triaminopyrimidine; the metal halide is zinc chloride or zinc bromide.

4. The hybrid metal halide crystal material with thermally induced jumping properties according to claim 1, characterized in that... The hybrid metal halide crystal material has a near-cubic bulk crystal appearance.

5. A hybrid metal halide crystal material with thermally induced jumping properties according to claim 1, characterized in that... When the metal halide is zinc chloride or zinc bromide, and the organic amine ligand is 2,4,6-triaminopyrimidine, the crystal chemical formulas are C4H9N5ZnCl4 or C4H9N5ZnBr4, respectively, denoted as TAPZnCl4 or TAPZnBr4, where TAP = 2,4,6-triaminopyrimidine. The unit cell parameters of the TAPZnCl4 are: a = b = 10.0660(1) Å, c = 9.7206(1) Å, α = β = 90 o , γ = 120 o ; The cell parameters of the TAPZnBr4 are: a = b = 10.4200(2) Å, c = 10.0671(3) Å, α = β =90 o , γ = 120 o ; The TAPZnCl4 and TAPZnBr4 exhibited broad-spectrum blue-white fluorescence emission under 360 nm excitation, with central peak positions of 455 nm and 465 nm, respectively. The DSC and TG tests of TAPZnCl4 and TAPZnBr4 showed that the jump start temperature ranges were 404-421 K and 460-475 K, respectively, and the decomposition temperatures were 510 K and 540 K, respectively. After replacing the halogen Cl with Br, the thermally driven jump start temperature increased by more than 50 K. The TAPZnCl4 crystal structure exhibits anisotropic thermal expansion coefficient upon heating, according to crystallography. a shaft and c The coefficient of thermal expansion of the shaft is 20.95 M·K. -1 and 73.17 M·K -1 ; c The coefficient of thermal expansion of the shaft is a 3.49 times the axis; The TAPZnBr4, after replacing the halogen Cl with Br, c The axial thermal expansion coefficient decreased to 66.30 M·K. -1 , a The axial thermal expansion coefficient increases to 22.40 M·K. -1 ; c axial thermal expansion coefficient and a The ratio of the axial thermal expansion coefficients decreased to 2.95 times.

6. A method for preparing a hybrid metal halide crystal material with thermally induced jumping properties as described in any one of claims 1 to 5, characterized in that... The specific steps are as follows: (1) Dissolve the metal halide and organic amine ligand in a hydrogen halide solution and obtain a milky white suspension by ultrasonic or magnetic stirring; (2) Add anhydrous methanol and deionized water to the suspension respectively, and stir magnetically under heating conditions until completely dissolved to obtain a clear solution; (3) After cooling to room temperature, the container containing the clear solution obtained in step (2) is sealed with a breathable seal to slow down the evaporation of the liquid. After standing and evaporating, blocky crystals are obtained.

7. The method for preparing a hybrid metal halide crystal material with thermally induced jumping properties according to claim 6, characterized in that... In step (1), the molar ratio of metal halide to organic amine ligand is 1:1; In step (1), the ratio of hydrogen halide solution to metal halide is hydrogen halide: metal halide = 6 ml: 1 mmol; In step (1), the hydrogen halide solution is a hydrobromic acid aqueous solution with a concentration of 40-48% or 99% hydrochloric acid. In step (2), when the volume ratio of hydrogen halide: anhydrous methanol: deionized water is 2:2:1, crystals with a side length less than 0.8 mm are grown; when the volume ratio of hydrogen halide: anhydrous methanol: deionized water is 3:2:2, crystals with a side length greater than 0.8 mm are grown. The heating temperature in step (2) is between 50 and 100 ℃; In step (3), the temperature is lowered to room temperature at a rate of 5 °C / min, the container containing the clear solution is sealed with a sealing film, and a hole is made with a needle tip. The solution is slowly evaporated at a rate of 0.02 ml / h at room temperature, and blocky crystals are obtained after 1-7 days.

8. The method for preparing a hybrid metal halide crystal material with thermally induced jumping properties according to claim 6, characterized in that... When the metal halide is zinc chloride and the organic amine ligand is 2,4,6-triaminopyrimidine, the specific steps for preparing hybrid metal halide crystals with thermo-induced jumping properties are as follows: Step 1: Weigh zinc chloride and 2,4,6-triaminopyrimidine in a molar ratio of 1:1 and place them in an open glass bottle. Add hydrochloric acid at a ratio of 6 ml to 1 mmol of zinc chloride. After sealing the bottle, stir it by sonication or magnetic stirring to obtain a milky white suspension. Step 2: Add anhydrous methanol and deionized water to the suspension according to the volume ratio of hydrochloric acid: anhydrous methanol: deionized water = 2:2:1 or 3:2:

2. Stir magnetically under heating conditions of 50~100 ℃ until completely dissolved to obtain a clear solution. Step 3: Slowly cool to room temperature, seal the open bottle with sealing film, and poke a few holes with a needle tip to slow down the evaporation rate. After standing for 1-7 days, block crystals are obtained. After vacuum filtration and drying at room temperature, 2,4,6-triaminopyrimidine zinc chloride crystal material is obtained.

9. The application of a hybrid metal halide crystal material with thermally induced jumping properties as described in any one of claims 1 to 5, characterized in that... It is used in protection circuits; the hybrid metal halide crystal is used as a thermal switching device in the protection circuit; the hybrid metal halide crystal is placed on a conductive heating plate as a thermal switching device, one end of the power supply of the circuit is connected to the conductive heating plate, and the other end is placed above the crystal; since the insulating crystal separates the electrodes, the circuit is in the off state at ambient temperature; when the temperature of the conductive heating plate reaches the crystal jump start temperature, the crystal jumps and the circuit is in the connected state.